The ZOONIVERSE is Expanding: Crowdsourced Solutions to the Hidden Collections Problem and the Rise of the Revolutionary Cataloging Interface. Issue 2 (3rd April 2018) - Barber, Samuel T.
Abstract: Experimental crowdsourced strategies pertaining to library resource description are becoming increasingly common. This research introduces the term "revolutionary cataloging interface" to describe the characteristics of crowdsourced metadata creation portals: capable of being learned during a 10–15 minute tutorial, requiring little or no previous cataloging experience, yet with demonstrated potential for producing robust and rich metadata with an impressive level of automated quality control. Focusing on a case study of Zooniverse's Operation War Diary, this paper investigates, explains, and assesses the potential of such innovations to meet successfully the challenges posed by Hidden Collections.